The Rhetoric of Persian News Headlines: A Case Study of Euronews - Monsefi, Roya; Tengku Mahadi, Tengku Sepora (Australian International Academic Centre (AIAC), 2017)
Media texts are often filled with strategies to persuade the readers and express ideas beyond the plain meaning of the words. The present study investigated the rhetorical features of Persian news headlines through the analysis of wordplay. A sample of 100 online news headlines of Euronews was selected. Wordplay was analysed because of its role in persuasion. The method was descriptive and the data was analysed on the basis of textual rhetorical analysis. Leigh’s (1994) framework including a taxonomy of different types of wordplay was adopted. Results revealed that the Persian news headlines of Euronews contained one or more clearly defined wordplay types. Tropes, or more specifically metonymies, were of the highest prevalence and wordplays such as oxymorons, parodies, anthimerias, polysyndetons, anadiploses, antimetaboles, epistrophes, climaxes and polyptotons were not present. The category of schemes encompassed the majority of unused wordplays. The discussion suggests that wordplay made the headlines more vivid and conspicuous.